Advantages of telmisartan pharmacotherapy in elderly patients with arterial hypertension and metabolic syndrome who have suffered an ischemic stroke - O. A. Osipova; A. N. Ilnitsky; E. V. Gosteva; S. G. Gorelik; L. V. Vasilyeva; N. I. Klyushnikov; N. I. Golovina; Yu. V. Tatarintseva; Yu. A. Lykov (Кардиоваскулярная терапия и профилактика)
Aim. To compare the effectiveness of telmisartan and perindopril in the treatment of elderly patients with arterial hypertension (AH) and metabolic syndrome (MS) who have suffered ischemic stroke (IS).Material and methods. 92 elderly patients with AH and MS who underwent IS (mean 68±4 years) were examined. Patients were randomly divided into pharmacotherapy groups: 47 patients took telmisartan (80 mg/day) and 45 — perindopril (10 mg/day). Fasting plasma glucose levels, insulin, leptin, total cholesterol, triglycerides, highand lowdensity lipoprotein cholesterol were determined, the HOMA-IR index was calculated, and daily monitoring was performed. Statistical processing was carried out using STATISTICA 10,0. The indicators are presented in the form of the median, interquartile ranges of Me (Q25%; Q75%), and mean ±SD. The comparison was carried out using the Wilcoxon rank criterion. The differences are significant at p<0,05.Results. After 12 months of observation in the telmisartan group, there was a significant decrease in the average daily systolic blood pressure (ВРs) from 152 (146; 156) to 129 (125; 134) mm Hg (p<0,01) and diastolic blood pressure from 89 (83; 96) to 76 (72; 84) mm Hg (p<0,05); reduction of НOMА-IR from 4,1 (3,3; 5,0) to 3,2 (2,7; 3,6) units (p<0,01), leptin from 14,3 (10,2; 17,7) to 11,7 (10,8; 13,6) ng/ml (p<0,01), triglycerides from 2,25 (1,90; 2,53) up to 2,05 (1,84; 2,05) mmol/l (p<0,05). In the perindopril group, ВРs decreased from 149 (144; 154) to 137 (131; 142) mm Hg (p<0,05), НOMА-IR (p=0,059), leptin from 14,4 (10,3; 18,0) to 13,0 (12,3; 13,8) ng/ml (p<0,05), triglycerides (p=0,056).Conclusion. Elderly patients with hypertension on the background of MS and a history of IS had significantly decreased ВРs and ВРd (according to the results of daily monitoring) after 12 months of telmisartan pharmacotherapy, decreased insulin resistance and the level of leptin and triglycerides in the blood serum.